La química en nuestros platos: los preservantes - Ángeles-Boza, Alfredo M. (2022)
Preservatives and preservation techniques give us access to the rich flavors of fresh food we all love while being away from the fields. Preservation techniques have been known since antiquity but they became more sophisticated after the Industrial Revolution as cities became more populous. Nowadays, preservatives are part of our daily life. They have become even more important as our society reaches for sustainability and food waste reduction. But the reader probably has a burning question: are they safe? The short answer is yes, they are safe. Let’s take a look at the history and chemistry of some of the most common chemicals used in food preservation techniques. With this information, the readers can decide on their own.